String Partition for Building Long BWTs - Adler, Enno; Böttcher, Stefan; Hartel, Rita (2025 Data Compression Conference (DCC))

IBB: Fast Burrows-Wheeler Transform Construction for Length-Diverse DNA Data - Adler, Enno; Böttcher, Stefan; Hartel, Rita; Steininger, Cedric Alexander (23rd International Symposium on Experimental Algorithms)

ITR: Grammar-based graph compression supporting fast triple queries - Adler, Enno; Böttcher, Stefan; Hartel, Rita (2024 Data Compression Conference (DCC))

QSGG: query simulation in grammar-compressed graphs - Böttcher, Stefan; Hartel, Rita; Peeters, Sven (Proceedings of The International Workshop on Semantic Big Data)

Pattern Search in Grammar-Compressed Graphs - Böttcher, Stefan; Hartel, Rita; Peeters, Sven (2020 Data Compression Conference (DCC) (Poster))

RECUT: RE-Compressing partially Unordered Trees - Böttcher, Stefan; Hartel, Rita (2018 IEEE International Conference on Big Data (Big Data))

A column-oriented text database API implemented on top of wavelet tries - Böttcher, Stefan; Hartel, Rita; Manuel, Jonas (DBKDA 2017)

S2CX: From relational data via SQL/XML to (Un-)Compressed XML - Böttcher, Stefan; Hartel, Rita; Wolters, Dennis (Information Systems)

Incremental updates on compressed XML - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas; Maneth, Sebastian (2016 IEEE 32nd International Conference on Data Engineering (ICDE))

OnlineRePair: A Recompressor for XML Structures - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas; Maneth, Sebastian (2015 Data Compression Conference)

ECST – Extended Context-Free Straight-Line Tree Grammars - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas; Jeromin, Markus (Data Science - 30th British International Conference on Databases, BICOD 2015)

Difference Computation for Grammar-Compressed XML Data - Böttcher, Stefan; Hartel, Rita; Thiele, Sebastian (Proceedings of the Second Australasian Web Conference)

Keyword Search on DAG-Compressed XML Data - Böttcher, Stefan; Brandenburg, Marc; Hartel, Rita (Proceedings of the Second Australasian Web Conference)

Efficient XML Keyword Search Based on DAG-Compression - Böttcher, Stefan; Hartel, Rita; Rabe, Jonathan (Database and Expert Systems Applications - 25th International Conference, DEXA 2014)

Schema-based Parallel Compression and Decompression of XML Data - Böttcher, Stefan; Feldotto, Matthias; Hartel, Rita (WEBIST 2013 - Proceedings of the 9th International Conference on Web Information Systems and Technologies, Aachen, Germany, 8-10 May, 2013)
Whenever huge amounts of XML data have to be transferred from a web server to multiple clients, the transferred data volumes can be reduced significantly by sending compressed XML instead of plain XML. Whenever applications require querying a compressed XML format and XML compression or decompression time is a bottleneck, parallel XML compression and parallel decompression may be of significant advantage. We choose the XML compressor XSDS as starting point for our new approach to parallel compression and parallel decompression of XML documents for the following reasons. First, XSDS generally reaches stronger compression ratios than other compressors like gzip, bzip2, and XMill. Second, in contrast to these compressors, XSDS not only supports XPath queries on compressed XML data, but also XPath queries can be evaluated on XSDS compressed data even faster than on uncompressed XML. We propose a String-search-based parsing approach to parallelize XML compression with XSDS, and we show that we can speed-up the compression of XML documents by a factor of 1.4 and that we can speed-up the decompression time even by a factor of up to 7 on a quad-core processor.

Fast Multi-update Operations on Compressed XML Data - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas (Big Data - 29th British National Conference on Databases, BNCOD 2013)

DAG - Index - A Compressed Index for XML Keyword Search - Böttcher, Stefan; Brandenburg, Marc; Hartel, Rita (WEBIST 2013 - Proceedings of the 9th International Conference on Web Information Systems and Technologies)

Implementing Efficient Updates in Compressed Big Text Databases - Böttcher, Stefan; Bültmann, Alexander; Hartel, Rita; Schlüßler, Jonathan (International Conference on Database and Expert Systems Applications)

Optimized XPath evaluation for Schema-compressed XML data - Böttcher, Stefan; Hartel, Rita; Heindorf, Stefan (ADC)

Generalizing and Improving SQL/XML Query Evaluation - Böttcher, Stefan; Bokermann, Dennis; Hartel, Rita (8th International Conference on Signal Image Technology and Internet Based Systems (SITIS'12))